Digital twin: Financial technology's next frontier of robo-advisor - Muhammad Anshari; Mohammad Nabil Almunawar; Masairol Masri (Journal of Risk and Financial Management, 2022)
This research examines the concept of a robo-advisor with digital twin capabilities for personal financial management. Using an exploratory study, the researchers developed an interactive and interpretive model that analyses the most critical variables to consider when designing the next level of financial robo-advisor through integrating digital twin concepts and applications. Primarily, it conducts an assessment and then reviews the data to propose a model that can serve as a baseline for future research. Related literature was explored, including peer-reviewed journal articles, case studies, periodicals, newspaper articles, and books. This study aims to assess the concept of digital twin (DT) as the next frontier of robo-advisor as a new wave of intelligent financial advisors in supporting the personalisation and customisation of financial technology (FinTech) services and management. Individuals who use a DT-enabled robo-advisor may find a significantly greater value for their financial management and well-being. A robo-advisor with DT enabled will no longer be an ad hoc financial advisory service but will evolve into a comprehensive and dynamic financial advisory service for users. The research presents several critical insights on financial robo-advisory with DT capabilities, transforming and optimising smart financial advisory.
Keywords: 650; artificial intelligence; digital twin; financial technology; personalisation; robo-advisor